2018
DOI: 10.3390/v10020083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mutations in the Hemagglutinin of H10N7 Viruses Isolated from Seals on Virus Replication in Avian and Human Cells

Abstract: Wild birds are the reservoir for low-pathogenic avian influenza viruses, which are frequently transmitted to domestic birds and occasionally to mammals. In 2014, an H10N7 virus caused severe mortality in harbor seals in northeastern Europe. Although the hemagglutinin (HA) of this virus was closely related to H10 of avian H10N4 virus, it possessed unique nonsynonymous mutations, particularly in the HA1 subunit in or adjacent to the receptor binding domain and proteolytic cleavage site. Here, the impact of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…S2). These results are consistent with other studies that also used biolayer interferometry analyses to determine binding affinity for avian-origin H10 viruses (27), and they are consistent with results for a study, using turkey erythrocytes expressing both SA␣2,3GA and SA␣2,6GA or only SA␣2,6GA receptors, of seal-origin H10 IAVs that showed significant binding ability to SA␣2,3GA and SA␣2,6GA (19). However, our results showed that the binding affinities to SA␣2,6GA could vary to some extent, depending on the virus strain, but sequence analyses for the reported HA receptor binding sites were mostly conserved among the isolates (Table S1).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…S2). These results are consistent with other studies that also used biolayer interferometry analyses to determine binding affinity for avian-origin H10 viruses (27), and they are consistent with results for a study, using turkey erythrocytes expressing both SA␣2,3GA and SA␣2,6GA or only SA␣2,6GA receptors, of seal-origin H10 IAVs that showed significant binding ability to SA␣2,3GA and SA␣2,6GA (19). However, our results showed that the binding affinities to SA␣2,6GA could vary to some extent, depending on the virus strain, but sequence analyses for the reported HA receptor binding sites were mostly conserved among the isolates (Table S1).…”
Section: Discussionsupporting
confidence: 91%
“…However, our results showed that the binding affinities to SA␣2,6GA could vary to some extent, depending on the virus strain, but sequence analyses for the reported HA receptor binding sites were mostly conserved among the isolates (Table S1). Of note, a mutation, Q220L (corresponding to 226 in H3 numbering), which was reported to have been acquired in the 220 loop of the HA receptor binding site during the subtype H10N7 IAV outbreaks among European seals, increased replication ability in mammalian cells (A549 cells) and retained replication efficiency in the avian cells (chicken embryo kidney primary cells) (19). This mutation seems to increase the binding affinity of avian-origin H10N7 IAV to SA␣2,6GA (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human infections with H10N7 were occasionally reported from Egypt (2004) and Australia (2010) [ 143 ]. Recent H10N7 AIV-associated natural outbreaks in harbor seals and experimental infection of ferrets emphasize that H10N7 may possess a zoonotic potential [ 144 , 145 , 146 ].…”
Section: Evolution and Epidemiology Of Iavmentioning
confidence: 99%